Fast overlap removal for location-related representation elements - Chen, Hongqian; Li, Hui (Neural computing & applications, 2022)
In order to resolve the issues with overlapping elements in location-related applications, an element adjustment method is proposed. This adjustment method can be implemented using a non-iterative algorithm which can significantly improve the processing efficiency of overlap removal. The method first sorts out all the elements according to the distance from the preset Starting Point. Repulsive offset adjustment is used for circular elements. It can be validated through theoretical derivation. Finally, the influencing factors of algorithm parameters are analyzed. Suggestions are given to further optimization of the algorithm. Experimental results show that it can effectively remove overlapping. The relative positional relationship among elements can be preserved to the greatest extent. User’s verifications and expert’s evaluation show that it can also achieve high recognition rate between the geographic region and its representation element.